2015
DOI: 10.1590/0103-6440201302282
|View full text |Cite
|
Sign up to set email alerts
|

Response of Human Pulps to Different In-Office Bleaching Techniques: Preliminary Findings

Abstract: This study evaluated a whitening effect and the likely side effect (tooth sensitivity and pulp response) of human teeth subjected to different in-office bleaching (IOB) techniques and materials, mainly the presence of calcium in the IOB materials. A calcium-free (CF) and a calcium-containing (CC) 35% hydrogen peroxide (HP) gels were evaluated. The CF was refreshed every 15 minutes, three times (CF 3-15) or in a single 45-min application (CF 1-45) at one bleaching appointment. The CC was used only in a single 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 21 publications
3
42
1
7
Order By: Relevance
“…A previous study of rat molars has shown that H 2 O 2 causes necrosis in the occlusal third of coronary pulp after one bleaching session . A similar outcome was found in a study of human teeth . These changes may be related to the observation that most patients report postoperative sensitivity after dental bleaching techniques, especially after the use of high concentrations of H 2 O 2 …”
Section: Introductionsupporting
confidence: 61%
“…A previous study of rat molars has shown that H 2 O 2 causes necrosis in the occlusal third of coronary pulp after one bleaching session . A similar outcome was found in a study of human teeth . These changes may be related to the observation that most patients report postoperative sensitivity after dental bleaching techniques, especially after the use of high concentrations of H 2 O 2 …”
Section: Introductionsupporting
confidence: 61%
“…The presence of calcium gluconate in bleaching gel minimizes the necrosis observed in human teeth after dental bleaching (Roderjan et al . ). This is because calcium can maintain a stable pH of the bleaching gel, besides preventing demineralization of the enamel, which would consequently reduce H 2 O 2 penetration and tooth sensitivity (Kossatz et al .…”
Section: Discussionmentioning
confidence: 97%
“…7,8,9 While laboratory testing is a very useful method to study the diffusion of the components of bleaching gels, such H 2 O 2 , into dental pulp, 10,11 clinical trials can provide reliable and direct evidence to guide clinicians in their choice of materials for in-office and at-home bleaching. 12,13,14,15 Hence, randomized controlled trials (RCTs) are considered the standard research design for the evaluation of health interventions.…”
Section: Introductionmentioning
confidence: 99%